Assessment of Genetic Diversity and Population Structure of Some Soft and Hard Wheat Varieties Based on SSR Marker - Fattah, Yousif M.; Tayib, Nergiz N. (Science Journal of University of Zakho, 2020)
Wheat (Triticum spp.) is one of the most important cereal crops in Iraq and the world. It includes many species and varieties. The two major cultivated species of wheat are, durum wheat (Tritium durum Desf.) which is tetraploid (2n= 28) and the common wheat (Triticum aestivum L.) which is hexaploid (2n = 42). Ten wheat varieties from both species were examined using ten Simple sequence repeat (SSR) markers (WMC17, WMC20, WMC21, WMC24, WMC25, WMC48, WMC50, WMC283, Xgwm11 and Xgwm626). Various genetic parameters were calculated using Power Marker V3.25 software. A total of 156 alleles were detected in both species. The gene diversity in wheat varieties from both species collectively varied from 0.85 to 1.00, which indicates considerable genetic diversity in the examined varieties. All markers used in this study were highly informative and the polymorphic information content (PIC) values were higher than 0.50 in all loci. Hence all markers are considered useful for genetic diversity studies in wheat’s populations. The dendrogram separated the populations into two main clades and many subgroups. Azadi variety was simplicifolious. This study confirms the discriminating power of SSR typing and its usefulness for comparison within hard and soft wheat populations.